Pelaksanaan Mekanisme Penanganan Tindak Pidana Penipuan di Polwiltabes Bandung Dikaitkan dengan Peraturan Polisi Nonor 8 Tahun 2021 Tentang Penanganan Tidak Pidana Berdasarkan Keadilan Restoratif - Noviyanti Nurjannah; Dey Ravena (Bandung Conference Series: Law Studies, 2023)
Abstract. Referring to Police Regulation Number 8 of 2021 concerning the Handling of Crimes based on Restorative Justice, the process of its application by investigators at the Bandung Polwiltabes, SP3 may only be issued after fulfilling special requirements, namely by attaching evidence that the victim's rights have been restored. But in fact, SP3 was issued by Bandung Polwiltabes investigators without attaching evidence of recovery of the victim's rights. This is of course very contradictory in the settlement of fraud cases based on Police Regulation Number 8 of 2021 concerning Handling of Crimes based on Restorative Justice. The purpose of writing this thesis is to analyze how the implementation of the mechanism for handling criminal acts of fraud in the Polwiltabes Bandung uses a restorative justice approach and how is the form of certainty for the restoration of victims' rights based on restorative justice related to Police Regulation Number 8 of 2021 concerning Handling of Crimes based on Restorative Justice. Types in this research is Nondoctrinal legal research or sociological juridical, namely research that is carried out directly by looking at the reality that exists in practice in the field, and is based on a study of the operation of law in society. The research method used by researchers is normative juridical. Data collection techniques use primary, secondary and tertiary legal materials. The mechanism carried out by the Bandung Polwiltabes Criminal Investigation Unit investigators in implementing restorative justice has helped resolve cases of criminal acts of fraud in the jurisdiction of the Bandung Polwiltabes. However, a different thing happened to Prison Number: LP/2624/XI/2020/JBR/POLWILTABES related to the criminal act of fraud for business capital/investment cooperation in the procurement of ammonia, in the end after the issuance of SP3 by Satreskrim Polwiltabes Bandung, obstacles were found related to evidence of restoration of victim's rights . The reported party fled while the fulfillment of the victim's right to compensation or compensation has not been fully obtained. In the implementation of restorative justice, investigators or investigators must first complete the material and formal requirements as stated in Articles 4 and 5 of the Republic of Indonesia Police Regulation No. 8 of 2021. Furthermore, regarding the document evidence of victim recovery, it has also been regulated in Article 15 paragraph (3). After all the requirements have been met, the new investigator or investigator can stop the investigation or investigation with reasons for the sake of law. Abstrak. Merujuk pada Peraturan Polisi Nomor 8 Tahun 2021 tetang Penanganan Tindak Pidana berdasarkan Keadilan Restoratif proses penerapannya oleh penyidik di Polwiltabes Bandung, SP3 hanya boleh dikeluarkan setelah memenuhi persyaratan khusus, yaitu dengan melampirkan bukti telah dilakukan pemulihan hak korban. Namun faktanya, SP3 dikeluarkan oleh penyidik Polwiltabes Bandung tanpa melampirkan bukti pemulihan hak korban. Hal ini tentunya sangat kontradiktif dalam penyelesaian perkara penipuan berdasarkan Peraturan Polisi Nomor 8 Tahun 2021 tetang Penanganan Tindak Pidana berdasarkan Keadilan Restoratif. Tujuan dari penulisan skripsi ini guna menganalisis terkait bagaimana pelaksanaan mekanisme penanganan tindak pidana penipuan di Polwiltabes Bandung dengan pendekatan keadilan restoratif dan bagaimana bentuk kepastian atas pemulihan hak korban berdasarkan keadilan restoratif dihubungkan dengan Peraturan Polisi Nomor 8 Tahun 2021 tetang Penanganan Tindak Pidana berdasarkan Keadilan Restoratif.Jenis pada penelitian ini adalah penelitian hukum Nondoktrinal atau yuridis sosiologis, yaitu penelitian yang dilakukan secara langsung dengan melihat kenyataan yang ada dalam praktik di lapangan, serta didasarkan atas kajian terhadap bekerjanya hukum di dalam masyarakat. Metode penelitian yang digunakan oleh peneliti adalah yuridis normatif. Teknik pengumpulan data menggunakan bahan hukum primer, sekunder dan tersier.Mekanisme yang dilakukan penyidik Satreskrim Polwiltabes Bandung dalam menerapkan restorative justice telah membantu menyelesaikan kasus tindak pidana penipuan pada wilayah hukum Polwiltabes Bandung. Akan tetapi, hal yang sngat berbeda terjadi pada Laporan Polisi Nomor : LP/2624/XI/2020/JBR/POLWILTABES terkait tindak pidana penipuan modal usaha/investasi kerjasama pengadaan Amoniak, pada akhirnya setelah diterbitkannya SP3 oleh Satreskrim Polwiltabes Bandung, ditemukan kendala terkait bukti pemulihan hak korban. Terlapor melarikan diri sementara pemenuhan hak korban atas ganti kerugian atau kompensasi belum didapatkan seutuhnya. Pelaksanaan keadilan restoratif, penyelidik atau penyidik harus terlebih dahulu melengkapi persyaratan-persyaratan baik materiil dan formiil sebagaimana tertuang dalam Pasal 4 dan Pasal 5 Peraturan Kepolisian Republik Indonesia No. 8 tahun 2021. Selanjutnya terkait dokumen bukti pemulihan korban juga telah diatur dalam Pasal 15 ayat (3). Setelah semua persyaratan terpenuhi, maka penyelidik atau penyidik baru dapat menghentikan penyelidikan atau penyidikan dengan alasan demi hukum.